2022
DOI: 10.1155/2022/1801099
|View full text |Cite|
|
Sign up to set email alerts
|

Study of Subfascial Endoscopic Perforator Surgery Combined with Endovenous Laser Treatment in the Treatment of Great Saphenous Varicose Veins

Abstract: Great saphenous varicose vein (GSVV) is a venous reflux disease of the lower extremity. In order to explore the clinical effect of subfascial endoscopic perforator surgery (SEPS) with endovenous laser treatment (EVLT) in the treatment of GSVV, 80 patients who underwent unilateral saphenous varicose surgery are analyzed. The operation results show that the patients who used SEPS + EVLT have less operation time and mean blood loss, shorter postoperative active time and hospitalization stay, better curative effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…1 Their clinical manifestations include superficial varicose veins, segmental cystic or columnar expansion of veins, eczema, as well as swelling, pain, hyperpigmentation, pruritus, and even ulcer of lower limbs. 2 The local tissue becomes deficient in nutrients and oxygen due to blood deposition in LEVVs, which could easily cause fatigue, pain, and swelling of the leg. 1,3,4 Long-term development can lead to eczema, edema, and skin ulcers.…”
Section: Introductionmentioning
confidence: 99%
“…1 Their clinical manifestations include superficial varicose veins, segmental cystic or columnar expansion of veins, eczema, as well as swelling, pain, hyperpigmentation, pruritus, and even ulcer of lower limbs. 2 The local tissue becomes deficient in nutrients and oxygen due to blood deposition in LEVVs, which could easily cause fatigue, pain, and swelling of the leg. 1,3,4 Long-term development can lead to eczema, edema, and skin ulcers.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%